In situ synthesis of stretchable and highly stable multi-color carbon-dots/polyurethane composite films for light-emitting devices. Issue 3 (7th January 2020) - Lian, Fei; Wang, Chuanxi; Wu, Qian; Yang, Minghui; Wang, Zhenyu; Zhang, Chi
Abstract : Stretchable, mechanically stable multi-color carbon-dots-based polymer films are in situ fabricated, and showed potential for application in optoelectronic devices. Abstract : Multi-color-emissive fluorescent polymer nanocomposite films have potential applications in optoelectronic devices. Herein, stretchable, mechanically stable multi-color carbon-dots-based films are in situ fabricated by condensation and aging of carboxylated polyurethane in the presence of various carbon sources. As-prepared CDs/PU films emit different colors covering from blue (414 nm) to red (620 nm) by tuning reaction conditions. Moreover, CDs are fixed and have good dispersion in the PU matrix due to the interactions of amine groups from the carbon sources with the carboxylate group of PU. Thus, phase separation of composite films can be avoided. And, more than 90% of their emission intensity is preserved after soaking in water for 30 days, aging for up to 6 h at 100 °C, and subjecting to several cycles of stretching and natural recovery. These advantages are encouraging for the use of CDs/PU composite films in solid-state lighting applications. Remote multi-color LEDs have been fabricated by placing a down-conversion layer of CDs/PU films separated through coating them on the same chips (emission at 365 nm), with Commission Internationale de l'Eclairage color coordinates of (0.22, 0.23), (0.43, 0.53), (0.49, 0.46), and (0.41, 0.28), respectively.